The Shamanic Roots of European Culture: Visions of the Otherworld and Ecstatic Battles from the Middle Ages to the Present Day - Barillari, Sonia Maura (Uniwersytet Wrocławski. Pracownia Badań nad Tradycją Oralną, 2017)
This paper aims to investigate the traces that shamanic thought and culture have left in European medieval texts. It is particularly interesting to note how many elements of this system of thought are preserved in medieval literary works by Christian authors. A privileged observatory is offered by visionary literature, in which converge many characteristic topoi of the shamanic imaginary. In this regard, there are very interesting descriptions of the Other World, its topography and inhabitants. Likewise, we also find some illuminating forms of access to the ecstatic experience: in relation to these I consider that the XII century represents an important borderline era, which later was most influential regarding the forms of search for the vision. With these premises it will be interesting to compare some forms of shamanic ecstasies attested in the modern age on European territory: an example is offered by night-time battles that some predestined people fight on specific days of the year against maleficent spirits in order to safeguard their own community. Italian benandanti and Romanian strigoi share the same mythical and symbolic horizons and offer numerous elements of reflection regarding the longue durée of some cultural phenomena.
Keywords: shamanic culture; medieval texts; visionary literature; Other World; Rumanian folklore; benandanti; strigoi